Re-Engineering Nigerian Economy through Human Capital Development: A Case of Manufacturing Firms in Southern Part of Nigeria - Uzochukwu, Onyeizugbe Chinedu; Matthew, Oguegbe Tochukwu; Olohi, Enaini Stella (Journal of Social Economics Research, 2020)
The poor economic situation of Africa especially Nigeria has attracted government efforts to re-engineer the economy through bilateral agreements with developed countries, trade, investment which unfortunately have been met with unproductive outcomes. Consequently, it has become imperative to explore possible means of re-engineering the economy especially in Nigeria through development of human capital. Hence, this study examines re-engineering Nigerian economy through human capital development: a case study of manufacturing companies. The study employed the descriptive survey research design. The population of the study was 828 employees from two manufacturing firms which are Innoson Vehicle Manufacturing Co. Ltd in Anambra state and Ibeto Group of Companies Ltd. in Rivers state, out of which 269 participants were used in the study. Data for the study were collected through the use of questionnaire. Data collected was analyzed using the Pearson Product Moment Correlation. Findings of the study indicated that the nature of relationship between skill development and corporate performance in Manufacturing Firms in Southern part of Nigeria is significantly positive. The study concluded that human capital development is an essential tool which improves the nation’s key assets (her citizens), in order to increase and reengineer economic growth and development. It is further recommended that government of Nigeria should inculcate and implement enhanced training and development programmes especially for the youths who have more workforce capacity so as to motivate them in contributing to the nation’s economic growth and development in all sectors.